Weak ties and the value of social connections for autistic people as revealed during the COVID-19 pandemic - Elizabeth Pellicano; Melanie Heyworth (Communications Psychology)
Abstract A diverse portfolio of social relationships matters for people’s wellbeing, including both strong, secure relationships with others (‘close ties’) and casual interactions with acquaintances and strangers (‘weak ties’). Almost all of autism research has focused on Autistic people’s close ties with friends, family and intimate partners, resulting in a radically constrained understanding of Autistic sociality. Here, we sought to understand the potential power of weak-tie interactions by drawing on 95 semi-structured interviews with Autistic young people and adults conducted during the COVID-19 pandemic. We analysed the qualitative data using reflexive thematic analysis within an essentialist framework. During the COVID-19 lockdowns, Autistic people deeply missed not only their close personal relationships but also their “incidental social contact” with acquaintances and strangers. These weak-tie interactions appear to serve similar functions for Autistic people as they do for non-autistic people, including promoting wellbeing. These findings have important implications both for future research into Autistic sociality and for the design of practical services and supports to enhance Autistic people’s opportunities to flourish.